-1
$\begingroup$

$$\frac{x+y}{xy}=2,\ \ \frac{x-y}{xy}=6$$

I am not understanding how to solve the equation. I tried dividing the whole equation by $xy$, but, that didn't work too. Any hint or help would be much appreciated.

$\endgroup$
1

4 Answers 4

8
$\begingroup$

Note that

$$\frac 1y+\frac 1x=2\tag 1$$ $$\frac 1y-\frac 1x=6\tag 2$$ Now $(1)+(2)$ gives you $$\frac 2y=8\Rightarrow y=\frac 14.$$

$\endgroup$
4
$\begingroup$

We have a system of equations:

$$\frac{1}{x}+\frac{1}{y}=2$$ $$\frac{1}{y}-\frac{1}{x}=6$$

From equation 1 we have,

$$y=\frac{x}{2x-1}$$

putting it in equation 2 we have,

$$x=-\frac{1}{2}$$

Putting $x=-\frac{1}{2}$ in $y=\frac{x}{2x-1}$, we get $y$ in terms of a compound fraction,

$$y=\frac{-\frac{1}{2}}{-\frac{2}{2}-1}$$

$$\implies y=\frac{1}{4}$$

$\endgroup$
1
  • $\begingroup$ You can verify them by putting them in original equations and see that whether they satisfies your system or not. I have checked already so I would place a solution set, called System's solution set. $$S=(-\frac{1}{2}, \frac{1}{4})$$ $\endgroup$ May 3, 2015 at 12:15
3
$\begingroup$
  • $x+y=2xy$
  • $x-y=6xy$

so:

$x-y=6xy=3*2xy= 3(x+y)$

so

$2x=-4y$

and

$x=-2y$

By replacing above equation in the first equation, we have:

$-2y+y=2*(-2y)*y$

so

$y=4y^2$

and finally:

$y=1/4$ and $x=-1/2$

$\endgroup$
0
$\begingroup$

$$\{^{\frac{x+y}{xy}=2}_ {\frac{x-y}{xy}=6}<=>$$ $$x=-\frac{1}{2}, y=\frac{1}{4}$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.